Application of leisure motivation scale to sport tourism - Yusof, Aminuddin; Mohd Shah, Parilah (The International Journal of the Humanities, 2008)
The purpose of this research was to examine the applicability of the Leisure Motivation Scale in determining the motives of sport tourists visiting a particular destination. Specifically, the study seeks to identify the motives of sport tourists in terms of the following dimensions: intellectual (the extent to which an individual is motivated to travel to be involved in activities such as exploring, discovering or creating), social ( the extent to which an individual travels because of the need for friendship and interpersonal relationships), competence-mastery ( the extent to which an individual engages in tourism activities that is challenging, achievement-oriented or competitive in nature), and stimulus-avoidance (the extent to which an individual needs to escape and get away form over-stimulating situations). Data for this study was collected quantitatively from 400 subjects using the Leisure Motivation Scale developed by Ragheb and Beard (1983). The second part of the instrument measures preferred destination attributes. It consists of a 23 pair semantic differential scale which measures various tourist destination attributes developed by Attle (1996). Data were analyzed using descriptive statistics and logistic regression. The results were discussed in light of earlier findings concerning sport tourist motivations and preferred destination attributes. Practical implications to tourism marketers were also discussed